The Management of Extrapulmonary Comorbidities and Treatable Traits; Obesity, Physical Inactivity, Anxiety, and Depression, in Adults With Asthma - McLoughlin, Rebecca F.; McDonald, Vanessa M. (Frontiers in Allergy, 2021)
Asthma is a complex and heterogenous disease characterized by variability in disease expression and severity. Multiple extrapulmonary comorbidities and treatable traits are common in people with asthma, and there is an increasing appreciation of how these may complicate asthma management. This review will discuss the prevalence and impact of extrapulmonary comorbidities/risk factors or “traits,” which have been found to co-exist in asthma (obesity, symptoms of depression and/or anxiety and physical inactivity), the impact these traits have on future outcomes (including exacerbation risk and quality of life) and asthma management, and how we should target treatment in asthma when these extrapulmonary traits are present.